The Effect of Interactive PowerPoint Media on Changes in the States of Matter on Elementary School Students' Learning Interest - Natira Alma; Laili Rahmi (The Future of Education Journal, 2026)
This study aims to examine the effect of using interactive PowerPoint media on the learning motivation of fourth-grade students at SD Negeri 003 Kabun. The study employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest design. The population and sample consisted of all 27 fourth-grade students at SD Negeri 003 Kabun, selected using the total sampling technique. The research instruments included a questionnaire on the use of interactive PowerPoint media and a learning motivation questionnaire developed using a five-point Likert scale. Prior to data collection, the instruments were tested for content validity, construct validity, and reliability. Data were analyzed using SPSS version 29 through descriptive statistics, normality tests, homogeneity tests, and hypothesis testing using a paired-samples t-test. The results showed that the mean score for the use of interactive PowerPoint media increased from 73.11 in the pretest to 77.48 in the posttest. Similarly, the mean score of students' learning motivation increased from 72.48 to 75.78 after the intervention. The normality test indicated that all data were normally distributed, while the homogeneity test confirmed homogeneous variances. The paired-samples t-test yielded a significance value (Sig. 2-tailed) of < 0.001, which was lower than the significance level of 0.05, indicating a statistically significant difference between the pretest and posttest conditions. Therefore, it can be concluded that the use of interactive PowerPoint media has a significant positive effect on the learning motivation of fourth-grade students at SD Negeri 003 Kabun. Interactive PowerPoint media creates a more engaging learning environment, enhances students' attention and participation, and fosters greater learning motivation throughout the instructional process.